Kajian evaluasi manfaat dan kontribusi dana APBN dalam pembangunan peternakan di Jawa Timur - Eko Nugroho (Faculty of Animal Science, Universitas Brawijaya, 2010)
The study aimed at analyzing the benefit of the national income and purchasing budget (APBN) in achieving livestock development program in East Java province and analyzing the contribution of APBN in the livestock development program in East Java. The results showed that the contribution of livestock sub-sector to the Product Domestic Regional Bruto (PDRB) of the agricultural sector in East Java province was relatively low (9.20-9.26%) as compared to other sub-sectors. In addition, the contribution of agricultural sector to the total of PDRB in East Java province was 17.44-17.22%. Although its contribution was relatively low, the APBN budget remained important to develop livestock sector in East Java province. Keywords: livestock development, East Java